Medical student appraisal of interactive computer-assisted learning programs embedded in a general pathology course. - Reid, W; Harvey, J; Watson, G; Luqmani, R; Harkin, P; Arends, M (2000)
Computer-assisted learning programs (CALs) were embedded in a course on general pathology for medical students at the University of Edinburgh Medical School. Students' reactions to the programs were evaluated. Students completed written questionnaires and were interviewed and observed as they used the CALs. Students liked the CALs and felt that they were integrated with other parts of their teaching and aided them in understanding the subject material. Different question styles were variably appreciated. The most useful aspects of the CALs were the interactive parts (questions and answers), summaries, pictures, learning at the individual's own pace, and question practice, especially with MCQs. Students found the CALs an effective learning tool, particularly when linked with other course components as a complement to, rather than a replacement for, other learning methods.